Estudo controlado sobre a produção da voz cantada em pacientes com Doença de Parkinson - Ferreira, Michelle de Melo [UNIFESP] (2019)
Introduction: Parkinson's disease (PD) is characterized not only by bradykinesia, stiffness and tremor, but also by impairments in voice and speech at different procedural levels. Recent studies have shown that music may not only aid gait but may have a similar effect on vocal behavior. However, it is not yet clear to what extent memory could interfere with the sharpness of the chanting by biasing such results. It is also unknown whether singing can be affected by the disease since speech and singing have some independent neural networks. Objective: To compare vocal production between speech and singing and to investigate if there is difference in the different cognitive abilities involved in singing between individuals with Parkinson's disease and healthy people. Method: In the present study, twenty patients with Parkinson's disease were compared with twenty healthy controls matched by sex, age and schooling with musical experience as closely as possible. A series of tests was applied to evaluate vocal abilities in speech and singing, sound-musical perception and short and long-term musical memory. Results: Speech tasks did not differ in the direction of prosodic intonation, but the magnitude of this variation was significantly lower in the DP group than in the control group. The vocal range was also reduced in the spoken voice and in the glissando due to the difficulty of emitting higher frequencies. When it was evaluated the vocal performance in the song "Happy Birthday" without accompaniment it was possible to observe a difficult melodic direction whereas in the condition with accompaniment this did not happen. The acuity of the intervals was similar between the groups and the Vocal Imitation Test showed no group differences. Discussion: The impairments on spoken voice may also reflect on sung voice. However, singing with accompaniment of a musical instrument or with another voice can aid in the vocal acuity of notes, intervals and melodic outlines. Conclusion: The results found in the present study suggest that the accompanying singing can be used as an intervention tool to improve voice and speech impairments in this population.